1983
DOI: 10.1093/cvr/17.3.145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of uridine supply on glycogen resynthesis after ischaemia in the isolated perfused rat heart

Abstract: Isolated rat hearts were subjected to 30 min low flow ischaemia (0.5 ml X min-1). During reperfusion, uridine (5 X 10(-5) mol X litre-1) was added to the perfusion medium for 30 min. The concentrations of creatine phosphate, adenine nucleotides, uridylic nucleotides and glycogen were determined at the end of the experiments. The purpose of this work was to study the effects of uridine supply on the concentration of energetic compounds during reperfusion recovery. Low flow ischaemia induced a breakdown of creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…In other reports using the heart and brain, researchers employed uridine by the perfusion and intraperitoneal injection, respectively (Benzi et al, 1984;Aussedat, 1983;Geiger and Yamasaki, 1954;Sapronov et al, 2000). The present study used another way for determining the uridine effect in in vivo model and revealed orally administrated uridine reduced the MCAO/reperfusion-induced brain damage.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In other reports using the heart and brain, researchers employed uridine by the perfusion and intraperitoneal injection, respectively (Benzi et al, 1984;Aussedat, 1983;Geiger and Yamasaki, 1954;Sapronov et al, 2000). The present study used another way for determining the uridine effect in in vivo model and revealed orally administrated uridine reduced the MCAO/reperfusion-induced brain damage.…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, it is possible that, as in the case of purine nucleosides, uridine may increase cell survival under ischemic insults through the action of UPase. In fact, uridine has been thought to be an alternative energy source in rat heart and brain during ischemic situations even though UPase's role for this has not been revealed yet (Geiger and Yamasaki, 1954;Aussedat, 1983;Benzi et al, 1984;Sapronov et al, 2000). Moreover, based on our previous finding, it is obvious that uridine blocks the ischemiclike insult-evoked death of astrocytes by preserving cellular ATP levels and in this scheme, UPase is involved (Choi et al, 2006).…”
Section: Introductionmentioning
confidence: 94%
“…are used fast depletion of glycogen also occurs but the restoration is faster and a large "supercompensation" (200 %) several hours following isoprenaline injection was shown by Towart et al (20). Since the restoration of glycogen could be accelerated by increasing the synthesis of uracil nucleotides via uridine supply, we suggested that resynthesis of cardiac glycogen could be in part limited by the actual intracellular concentration of UDPG (uridine diphosphoglucose): the substrate of the ultimate step of glycogen synthesis (3,2).…”
Section: Introductionmentioning
confidence: 72%
“…The adenine nucleotide contents were measured using a previously described HPLC method [22]. Briefly, the column used was a Partisil-10-ODS-2-Whatman, the mobile phase was sodium pyrophosphate-phosphoric acid 25 mM, pH = 5.75 and the flow rate was 1.7 ml/min.…”
Section: Biochemical Determinationsmentioning
confidence: 99%